(untitled) (BIRDEM Medical Journal, 2016)
Background: Elevated level of serum alanine aminotransferase (ALT) is not uncommon in routine laboratory test. This study was aimed to find out the aetiology of asymptomatic raised ALT in hospitalized type 2 diabetes mellitus (T2DM) patients Methods: This cross-sectional study was done in BIRDEM over a period of six month. T2DM patients having asymptomatic raised serum ALT were evaluated clinically and by laboratory tests. Results: Total number of patients was 53. Among them male were 39 and female were 14. Male and female ratio was 2.8:1. Mean age was 49.2±7.9 years. Mean body mass index (BMI) was 25.5±5 kg/m2. Among the study subjects, 25 (47.2%) were overweight and 16 (30.2%) were obese. Hypertension, hepatomegaly and dyslipidaemia were present in 29 (54.7%), 11 (20.8%) and 36 (67.96%) cases respectively. Non-alcoholic fatty liver disease (NFALD) was the commonest (37, 69.8%) aetiology for raised ALT in this study. Seropositivity for hepatitis B virus (HBV) surface antigen (HBsAg) and antibody against hepatitis C virus (anti-HCV) were present in 7 and 5 cases respectively. In 4 cases cause could not be identified. Most of the cases with >5 times raised ALT had hepatitis B or C infection. Conclusion: Elevation of serum ALT is common in T2DM patients. NAFLD is the commonest cause followed by hepatitis B and C virus infection. Birdem Med J 2016; 6(1): 32-35